3-D Inversion of Gravity Data Using Iterative Calculation for Subsurface Modeling of Mt. Pandan, East Java, Indonesia - Waskito Aji; E. J. Wahyudi; D. Santoso; W. G.A. Kadir (Jurnal Geofisika, 2018)
Mount Pandan is one of the volcanoes located in East Java.There was an earthquake with magnitude 4.2 onThursday, June 25, 2015, at 10.35 pm located in the area of Mount Pandan. The earthquake indicates the active tectonic of Mount Pandan. In addition, Mount Pandan is one of eleven geothermal prospects in East Java. Thus, it is interesting to do a study related to the geological condition of Mount Pandan. So far, most studies have discussed the related surface geology of Mount Pandan. This study aims to provide information related to the subsurface condition of Mount Pandan based on gravity data. In this research, gravity data inversion modeling technique is used to image the subsurface condition of Mount Pandan. The inversion technique used is non linear inversion with iterative calculation method. In this modeling scheme, the model to be determinedis a layer boundary depth model of two layers of rock based on gravity anomaly data. In each layer the rock is assumed to be composed of a set of rectangular prisms with a certain dimension. A collection of prisms representing the rock layers is then computed by the model response and evaluated by comparing it to the observed data. From this evaluation, a modication of the length of the prism is made so thatthe boundary layer model will change. The process of evalu ation and modication of the model is done iteratively until it reaches the number of predened iterations. The result obtained from this gravity inversion modeling is a model of the subsurface boundary of Mount Pandan. The subsurface model obtained is the existence of a formation resembling a rock intrusion, in this case interpreted as an andesitic rockthat intrudes overlying rock layers. This intrusive formation lies at the peak of Mount Pandan and is continuously to the north, with the undisturbed intrusion located around the summit of Mount Pandan.